Introduction to and Discussion Summary of William Tay's Colonialism, Cold War Era, and Marginal Space: The existential Conditions of Four Decades of Hong Kong Literature - Birus, Hendrik (Surfaces, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces William Tay's "Colonialism, the Cold War Era, and Marginal Space: The Existential Conditions of Four Decades of Hong Kong Literature" and reports on the central concerns that emerged in its discussion.